Tre økonomiske professorers teologi - Kærgård, Niels (Kirkehistoriske Samlinger, 1997)
The three economists Harald Westergaard (1853-1936), Laurits V. Birck (1871-1933) and Jens Warming (1873-1939) were all active as professors at The University of Copenhagen at the same time; in fact they were three out of four professors in economics during the period 1919-1924. (Jens Warming became professor in 1919 and Harald Westergârd had retired in 1924). Even though they were economists all of them participated intensively in the ecclesi-astical debate of the time. Harald Westergaard was a main figure in the circles, who established churches in the working-class districts of Copenhagen and he was at the same time very active in Christian movements for social reforms. He was very interested in alcohol politics and the temperance movement, too. During the whole period 1885-1936 he was the leading layman in the Danish church; he was a member of a considerable number of committees and organisations, he gave a countless number of talks and lectures and wrote an equal number of articles and paragraphs about religious questions. Jens Warming was a rather strange person. His contemporaries considered him as being a bit odd. He worked carefully with voluminous statistical descriptions of Danish society. But in between there were theoretical arguments years ahead of his time. His Christianity was characterized by a combination of naïveté and a matter-of-fact outlook e.g. in long discus-sions of God’s meaning of the economic cycles. L.V. Birck was besides his work at the university active in journalism and politics - he was a member of the Danish parliament 1903-1910 and 1918-1920 and played an important role in Danish politics a number of times. He wrote under the signature of »Dr. Aloysius« a number of newspaper articles and in 1917 a small book about religious questions. He was an unorthodox religious man and found valuable elements both in Christianity and Buddhism. In the article the careers and religious activities of these three persons are described. It is shown that there were important links between their religious attitude and their economic research; it is for instance remarkable that at the same time when Harald Westergaard was saved, his research changed rather drastically from pure mathematical economic theory to statistical investigation of the mortality rates in different social groups.